Evaluation of the Effectiveness of Student Worksheets (LKPD) in Differentiated Learning in Economics Activities at Nusantara Indah High School - Anna Marganingsih; Emilia Dewiwati Pelipa; Yulia Suriyanti; Dessy Triana Relita; Siti Marsitoh (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to evaluate the effectiveness of using Student Worksheets (LKPD) in differentiated learning on economic activities in senior high schools. The background of this study is based on the importance of innovative teaching materials that can adapt to the diverse learning needs of students in accordance with the principles of differentiated learning in the Independent Curriculum. The research method used is a quantitative descriptive method with data analysis techniques in the form of calculating averages, percentages, and effectiveness tests. The research respondents consisted of ninth-grade students of SMA Nusantara Indah who used differentiation-based LKPD in the process of learning economic activities. The results of the study indicate that the use of differentiated LKPD is effective in increasing active participation, understanding of economic concepts, and student learning motivation. Thus, differentiation-based LKPD can be used as an alternative innovative teaching material that supports the optimal achievement of learning objectives at the senior high school level.